2020
DOI: 10.3390/ijerph17031061
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Strontium onto Adaxial and Abaxial Cuticle of Photinia serrulata Leaf

Abstract: Leaf cuticle sorption is one important process for the uptake of environment pollutants in plants, and mixed powder including adaxial and abaxial cuticle is generally used to demonstrate the sorption behavior. However, the difference of adaxial and abaxial cuticle on plant cuticle sorption is not well understood. Abaxial cuticle (PAC) and adaxial cuticle (PBC) were isolated from hypostomatic Photinia serrulata to investigate their adsorption of a model radionuclide (strontium). The elemental composition and FT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Besides its ornamental function, numerous researches have confirmed that P. x fraseri has robust resistance to drought (Ugolini et al, 2014;Toscano et al, 2016;Kösa, 2023) and to extreme temperature (Haynes et al, 1992), and also has medicinal benefits (Song et al, 2021). The relatively high specific leaf area, compared with other common shrub species (Wang et al, 2016), assists P. x fraseri in developing considerable dust retention ability (Li et al, 2020). Its ability to resist cold weather conditions and air pollution, it is a plant that can grow even in urban areas with arid soil, and poor drainage (Akdemir et al, 2016;Wu et al, 2019;Kösa, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Besides its ornamental function, numerous researches have confirmed that P. x fraseri has robust resistance to drought (Ugolini et al, 2014;Toscano et al, 2016;Kösa, 2023) and to extreme temperature (Haynes et al, 1992), and also has medicinal benefits (Song et al, 2021). The relatively high specific leaf area, compared with other common shrub species (Wang et al, 2016), assists P. x fraseri in developing considerable dust retention ability (Li et al, 2020). Its ability to resist cold weather conditions and air pollution, it is a plant that can grow even in urban areas with arid soil, and poor drainage (Akdemir et al, 2016;Wu et al, 2019;Kösa, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, these results must be assessed carefully as the leaf dehydrates during the measurements, which has been reported to cause cuticular conductance to vary (Boyer, 2015b). Nevertheless, studies on isolated cuticles indirectly support the hypothesis of different surfaces having different g cw , showing different physical and chemical properties for adaxial and abaxial sides (Onoda et al ., 2012; Li et al ., 2020) as well as different permeabilities for adaxial and abaxial isolated cuticles (Karbulková et al ., 2008). However, there is no clear relationship between cuticular conductance and cuticle composition and thickness (Yeats & Rose, 2013; Duursma et al ., 2018), nor for isolated cuticle permeability and in planta cuticular conductance (Kerstiens, 2006; Zhang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%